Protocol for a phase IV double-blind randomised controlled trial to investigate the effect of the 13-valent pneumococcal conjugate vaccine and the 23-valent pneumococcal polysaccharide vaccine on pneumococcal colonisation using the experimental human pneumococcal challenge model in healthy adults (PREVENTING PNEUMO 2). Issue 7 (7th July 2022) - Liatsikos, Konstantinos; Hyder-Wright, Angela; Pojar, Sherin; Chen, Tao; Wang, Duolao; Davies, Kelly; Myerscough, Christopher; Reine, Jesus; Robinson, Ryan E; Urban, Britta; Mitsi, Elena; Solorzano, Carla; et al.
Abstract : Introduction: Despite widely available vaccinations, Streptococcus pneumoniae (SPN) remains a major cause of morbidity and mortality worldwide, causing community-acquired pneumonia, meningitis, otitis media, sinusitis and bacteraemia. Here, we summarise an ethically approved protocol for a double-blind, randomised controlled trial investigating the effect of the 13-valent pneumococcal conjugate vaccine (PCV13) and the 23-valent pneumococcal polysaccharide vaccine (PPV23) on pneumococcal nasopharyngeal colonisation acquisition, density and duration using experimental human pneumococcal challenge (EHPC). Methods and analysis: Healthy adult participants aged 18–50 years will be randomised to receive PCV13, PPV23 or placebo and then undergo one or two EHPCs involving intranasal administration of SPN at 1-month post-vaccination with serotype 3 (SPN3) and 6 months with serotype 6B (SPN6B). Participants randomised to PCV13 and placebo will also be randomised to one of two clinically relevant SPN3 strains from distinct lineages within clonal complex 180, clades Ia and II, creating five study groups. Following inoculation, participants will be seen on days 2, 7, 14 and 23. During the follow-up period, we will monitor safety, colonisation status, density and duration, immune responses and antigenuria. The primary outcome of the study is comparing the rate of SPN3 acquisition between the vaccinated (PCV13 or PPV23) and unvaccinated (placebo) groups as defined by classical culture. Density and duration of colonisation, comparison of acquisition rates using molecular methods and evaluation of the above measurements for individual SPN3 clades and SPN6B form the secondary objectives. Furthermore, we will explore the immune responses associated with these vaccines, their effect on colonisation and the relationship between colonisation and urinary pneumococcal antigen detection. Ethics and dissemination: The study is approved by the NHS Research and Ethics Committee (Reference: 20/NW/0097) and by the Medicines and Healthcare products Regulatory Agency (Reference: CTA 25753/0001/001–0001). Findings will be published in peer-reviewed journals. Trial registration number: ISRCTN15728847, NCT04974294 .